Effects of Mulching on Yield and Quality of Tomato Varieties - M. M. H. Tipu; M. Amin; M. Dhar; Md. Amirul Alam (STM Journals, 2014)
A field experiment was conducted at the Regional Agricultural Research Station, Hathazari, Chittagong to study the effect of different mulch materials on the yield and quality of tomato. rice husk mulch was found superior to sawdust, garden leaves and black polyethylene mulch in producing higher yield of tomato. Higher number of fruits per plant and maximum yield was recorded with rice husk which was 17.93% higher than the control (without mulch). BARI Tomato 14 in combination with rice husk produced highest yield (79.74 t/ha) highest TSS (6.67).